An unusual cause of haemoptysis and headache: cryptococcosis - How, Soon Hin; Kuan, Yeh Chunn; Ng, Teck Han; Ramachandran, Kalavathy; Abdul Rani, Mohammed Fauzi (College of Pathologists, Academy of Medicine Malaysia, 2008)
Pulmonary cryptococcosis can be clinically silent in non-HIV infected patients but can also present as nodules and masses on the chest radiograph, which can be mistaken for tuberculosis or lung cancer. Common symptoms include fever and cough, and uncommonly haemoptysis. This report illustrates a non-HIV infected patient whose main complaint was haemoptysis and headache. He was diagnosed with pulmonary cryptococcosis from biopsy of an endobronchial mass found on flexible bronchoscopy. Disseminated cryptoccoccal infection should be considered as a differential diagnosis in non-HIV infected patients presenting with haemoptysis and headache. Early recognition and administration of appropriate therapy will improve clinical outcome in these patients.